2012
DOI: 10.1042/bj20120787
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide signalling pathway in Duchenne muscular dystrophy mice: up-regulation of L-arginine transporters

Abstract: SYNOPSIS Duchenne muscular dystrophy (DMD) is an incurable, rapidly-worsening neuromuscular degenerative disease caused by the absence of dystrophin. In skeletal muscle, lack of dystrophin disrupts the recruitment of neuronal nitric oxide synthase (nNOS) to the sarcolemma thus affecting nitric oxide (NO) production. Utrophin is a dystrophin homolog which expression is greatly upregulated in the sarcolemma of dystrophin-negative fibers from mdx mice, a mouse model of DMD. Although cardiomyopathy is an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…Immunofluorescence labeling revealed that nNOS was localized in the cytoplasm, in a striated pattern, and in the nucleus and was not specifically enriched at the sarcolemma of WT or mdx cardiomyocytes at rest (Fig. S1), in agreement with previous reports (33,34). Moreover, stretch did not lead to membrane recruitment of nNOS or otherwise discernibly alter nNOS localization in either WT or mdx cells (Fig.…”
Section: Stretch-induced Nnos Phosphorylation Is Impaired In Dystrophin-supporting
confidence: 79%
“…Immunofluorescence labeling revealed that nNOS was localized in the cytoplasm, in a striated pattern, and in the nucleus and was not specifically enriched at the sarcolemma of WT or mdx cardiomyocytes at rest (Fig. S1), in agreement with previous reports (33,34). Moreover, stretch did not lead to membrane recruitment of nNOS or otherwise discernibly alter nNOS localization in either WT or mdx cells (Fig.…”
Section: Stretch-induced Nnos Phosphorylation Is Impaired In Dystrophin-supporting
confidence: 79%
“…28,29 Neuronal NOS (nNOS) interacts with dystrophin-associated glycoprotein complex at the sarcolemma in skeletal myocytes, and this association is lost in dystrophin deficiency. 28 However, in cardiomyocytes isolated from the mdx mouse, nNOS does not colocalize with dystrophin 30,31 but instead colocalizes with the ryanodine receptor 2 (RyR2) at the sarcoplasmic reticulum. 32 Endothelial NOS localizes to the Golgi complex and the sarcolemma caveolae.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, Nos may also directly affect transcriptional activation of effector genes (Caceres et al, 2011). Human and mice ventricular myocardial sections show a similar SR-related pattern of nNos (Ramachandran et al, 2013; Xu et al, 1999). Interestingly, the slower heart rate of Nos RNAi flies was reversed in Dys −/− mutant background, so that Dys −/− ; Hand > Nos RNAi flies exhibited a significant decrease in both diastolic and systolic intervals.…”
Section: Discussionmentioning
confidence: 80%